2017
DOI: 10.1038/s41598-017-10101-x
|View full text |Cite
|
Sign up to set email alerts
|

The MC4R genotype is associated with postpartum weight reduction and glycemic changes among women with prior gestational diabetes: longitudinal analysis

Abstract: The genetic variants near the Melanocortin-4 receptor gene (MC4R), a key protein regulating energy balance and adiposity, have been related to obesity and glucose metabolism. We aimed to assess whether the MC4R genotype affected longitudinal changes in body weight and glucose metabolism biomarkers among women with prior gestational diabetes mellitus (GDM). The MC4R genotype, postpartum weight reduction, and glycemic changes between after delivery and pregnancy were assessed in a cohort of 1208 Chinese women wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…MC4R has been associated with key components of appetite, food intake, nutrient absorption, thermogenesis, energy expenditure, insulin secretion, obesity, and lipid metabolism (37). It is indicated that MC4R rs6567160 is associated with postpartum weight reduction and glycemic changes among women with prior GDM (38). Moreover, a significant correlation was observed between lipid parameters and MC4R rs17782313 (39).…”
Section: Discussionmentioning
confidence: 99%
“…MC4R has been associated with key components of appetite, food intake, nutrient absorption, thermogenesis, energy expenditure, insulin secretion, obesity, and lipid metabolism (37). It is indicated that MC4R rs6567160 is associated with postpartum weight reduction and glycemic changes among women with prior GDM (38). Moreover, a significant correlation was observed between lipid parameters and MC4R rs17782313 (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GWAs demonstrated MC4R to be one of the genes, which associates with common obesity [4,5]. The common polymorphism rs17782313 has recently been found to be unequivocally associated with obesity-related phenotypes in adults and children in different ethnicity and age groups [9,10,15].…”
Section: Discussionmentioning
confidence: 99%
“…have evidenced the association of common variants of several genes with obesty and other measurements of obesity [2,3]. Among these genes, the melanocortin-4 receptor (MC4R) gene has been considered to confer obesity risk [4,5]. MC4R gene (18q22) is a 322-amino acid; which belongs to the family of seventransmembrane, G-protein-linked receptor involved in central regulation of energy homeostasis, such as hypothalamus, brainstem, and other brain dopamine-rich regions [6][7][8].…”
Section: Introduction mentioning
confidence: 99%
“…Lorcaserin, a 5-HT2CR agonist used as anti-obesity drug, decreases glycemia by acting on MC4R cholinergic neurons (Burke et al 2017). Interestingly, an association has been found between MC4R genotype and postpartum glycemic changes in humans, thus highlighting the relevance of MC4R in glucose metabolism in humans (de Carvalho et al 2017). Cholinergic parasympathetic MC4R neurons, such as those localized in the dorsal motor nucleus of the vagus (DMV) control insulin levels and gastric motility (Rossi et al 2011, Richardson et al 2013.…”
Section: Mc4r Neuronsmentioning
confidence: 99%